Increased Cardiac Troponin-T in Patients without Myocardial Infarction - M. Ya. Krasnoselsky; Ye. V. Koshkina; N. M, Fedorovsky; Ye. V. Goryacheva; A. A. Polupan; A. A. Arefyev; M. Z. Bratanova (Общая реаниматология)
There have been recently reports on elevated levels of cardiac troponins in patients without acute myocardial infarction (AMI). The purpose of the study was to analyze final diagnoses in patients with elevated cardiac troponin-T levels without clinical manifestations and characteristic ECG changes in AMI. Subjects and materials. The study included 72 patients (48 males and 24 females whose age ranged from 54 to 87 years (mean 69.8±11.2 years)). The criterion for inclusion was increased cardiac troponin-T; the primary criteria for exclusion were AMI-specific anginal pains and characteristic ECG changes (ST-segment elevation, abnormal Q waves). The definitive diagnosis of AMI was established only in 29 (40.3%) patients; the remaining 43 patients were diagnosed as having the following diseases: sepsis (n=21), cancer (n=10), diabetic nephropathy with chronic renal failure (n=6), cerebral infarction (n=4), and B12-deficiency anemia (n=2). In deceased patients, the level of troponin-T was higher than that in those who was discharged from hospital irrespective of the underlying disease. Results. There was a direct correlation between the level of cardiac troponin-T and the SAPS II index that reflects the general condition of a patient (r=0.44; p=0.0001) and an inverse correlation between the former and the left ventricular ejection fraction (r=-0.45; p=0.003). Conclusion. Thus, despite its cardiac specificity and its detection in the blood of critically ill patients without other manifestations of AMI, cardiac troponin-T is not a specific symptom of AMI, but suggests the severity of the disease, possibly, with the involvement of the myocardium in the pathological process. Key words: cardiac troponins, myocardial infarction, multiple organ dysfunction, systemic inflammatory reaction.